Assessment of Physicochemical and Sensory Characteristics of Commercial Sparkling Wines Obtained Through Ancestral and Traditional Methods - Arnau Just-Borràs; Monserrat Alday-Hernández; Aitor García-Roldán; Marco Bustamante; Jordi Gombau; Pedro Cabanillas; Nicolas Rozès; Joan Miquel Canals; Fernando Zamora (Beverages, 2024)
Sparkling wines produced using the ancestral method, also known as Pét-Nats, are gaining more and more market share these days. However, scientific information on these wines is very scarce. The aim of this study was therefore to compare the physicochemical composition and sensory characteristics of a representative selection of commercial sparkling wines produced using the ancestral and traditional methods. Ancestral sparkling wines were more heterogeneous than traditional sparkling wines, as some of them showed lower internal pressure, higher turbidity, higher color intensity and lower effervescence. These differences are probably due to the fact that the protocol for making sparkling wines using the ancestral method is not as well defined as that for traditional sparkling wines. However, the ancestral method has the advantage of being able to work with riper grapes and a lower sulfur dioxide dosage.